Jorge Semprún : the Spaniard who survived the Nazis and conquered Paris - Fox Maura, Soledad (The Cañada Blanch / Sussex Academic Studies on Contemporary Spain, 2017)
"Spanish by birth, Parisian by adoption, Semprún (1923-2011) was a legendary figure on the front lines of twentieth-century European history. During the first half of his life he was an exile of the Spanish Civil War, a member of the French Resistance, a Nazi camp survivor, and clandestine agent for the Spanish Communist Party. After repeatedly risking his life from the 1930s to the 1960s, he reinvented himself as a prolific writer who turned the extraordinary material from his own life into a series of autobiographical novels, beginning with The Long Voyage, his 1963 masterpiece about his deportation to Buchenwald. Semprún was equally at home amongst the madrileños of his childhood, fellow prisoners of the Buchenwald concentration camp, politicians, and artists and writers, such as his close friend Yves Montand or Gabriel García Márquez. He is best known internationally as a prize-winning novelist and memoirist, and an Oscar-nominated screenwriter. In collaboration with Alain Resnais and Costa-Gavras he wrote the screenplays for, respectively, La guerre est finie and Z. In Spain, his extraordinary achievements were recognized when in 1988 he was named Minister of Culture. The research for this biography draws on archival materials from Spain, France, Germany, the United States and Russia; it includes many interviews with family members, close friends, politicians, and artists including former Spanish Prime Minister Felipe Gonzalez, and film director Costa Gavras"--